2008
DOI: 10.1007/s11999-008-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Cage Survival and Analysis of Factors Related to Failure

Abstract: The reported results of acetabular cage reconstruction for pelvic deficiency are widely variable. Our primary question was: what is the survivorship of cage reconstruction with a primary end point of cage revision and secondary end points of radiographic loosening and any reoperation? Secondary questions were: which factors predict cage failure, and what is the functional outcome (SF-36, WOMAC, Harris hip score) of this reconstructive method? We reviewed 72 cage reconstructions in 68 patients. Minimum followup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 38 publications
2
30
1
1
Order By: Relevance
“…We still do not have long term followup of the use of TM cups, and the selection criteria and outcome assessment vary considerably among studies (Table 3). Nevertheless, cages had no advantage over TM cups regarding mechanical failure rates at a mean followup of 4 to 5 years, despite their potential better initial stability [1,9,20]. Other studies that evaluated the performance of TM cups for more heterogeneous groups of acetabular defects had failure rates comparable to that of our series [5,13,21,22].…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…We still do not have long term followup of the use of TM cups, and the selection criteria and outcome assessment vary considerably among studies (Table 3). Nevertheless, cages had no advantage over TM cups regarding mechanical failure rates at a mean followup of 4 to 5 years, despite their potential better initial stability [1,9,20]. Other studies that evaluated the performance of TM cups for more heterogeneous groups of acetabular defects had failure rates comparable to that of our series [5,13,21,22].…”
Section: Discussionmentioning
confidence: 45%
“…Acetabular component revision in the face of large contained bone defects with no more than 50% host bone contact has been traditionally treated with roof reinforcement rings or antiprotrusio cages, associated with substantial complication and failure rates [9,20]. Trabecular Metal TM cups may offer a reasonable treatment alternative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cage is constructed from titanium alloy and thought to transfer load off the acetabular socket and onto the peri-acetabular bone through adjustable illeal and ischial flanges that provide intimate contact with native bone when secured to the pelvis using cancellous screws. 10,17 Cages protect underlying bone graft from lysis and permit remodeling with native bone. True survivorship of cages is unclear but has ranged from less than 70% to 100% according to Sembrano et al who report that the end-points of each study varied depending on time of cage removal, evidence of radiographic loosening, and reason for revision.…”
Section: Bone Cages With Allograftsmentioning
confidence: 99%
“…True survivorship of cages is unclear but has ranged from less than 70% to 100% according to Sembrano et al who report that the end-points of each study varied depending on time of cage removal, evidence of radiographic loosening, and reason for revision. [17][18][19][20][21][22][23][24][25][26][27] Regis et al reported an 87% (49/56) survival rate at a mean follow-up of 11.7 years in type IIIA (32%) and IIIB (68%) hips using cages and structural allografts using radiographic evidence of bone ingrowth and remodeling as the primary endpoint. 28 The major disadvantage of cages includes high complication rates previously reported by multiple authors.…”
Section: Bone Cages With Allograftsmentioning
confidence: 99%